Social Media Utilization Strategy for Marketing Makeup Artist (MUA) Services among PKK Women in Sumber Agung Village, North Bengkulu Regency - Andreani Kinata; Susi Handayani; Parwito Parwito; Edi Susilo (Perkumpulan Dosen Muda Bengkulu, 2026)
Social media offers a low-cost opportunity for rural service-based microenterprises to expand market reach and build customer trust. This community service initiative aimed to formulate a practical social media marketing strategy for members of the Family Welfare Empowerment (PKK) group in Sumber Agung Village, Arma Jaya District, North Bengkulu Regency who provide or are interested in developing makeup artist (MUA) services. The program formulation was conducted through market mapping, platform selection, content planning, local branding, customer communication design and a four-week training plan. The resulting strategy differentiates platform functions: Instagram as a visual portfolio and branding channel, TikTok for short-form reach, Facebook for local community exposure and WhatsApp Business for service conversion and customer communication. Content priorities include before-and-after portfolios, local bridal makeup, short educational tips, geotagging, local hashtags, testimonials and transparent service packages. The training plan emphasizes smartphone photography, business-account optimization and short-video production. This integrated strategy provides a practical framework for strengthening the visibility, credibility and market accessibility of village-based MUA services while supporting women’s creative-economy activities